SELF-EFFICACY ON ANXIETY LEVELS IN FACING OF COMPETENCY TESTS FOR STUDENTS OF THE NURSE PROFESSION (Proceedings OPTIMAL, 2024)
Self-efficacy is an individual's belief in ability. Self-efficacy plays an important role in many aspects of life, including education, work, health, and interpersonal relationships. Individuals with high self-efficacy tend to be more motivated, try harder, and are more resistant to stress and failure. Anxiety is an emotional response to a perceived threat, which can be tangible. Anxiety is often characterized by feelings of fear, worry, and tension, and can be accompanied by physical symptoms such as increased heart rate, excessive sweating, and shortness of breath. The purpose of this study is to determine the relationship between self-efficacy and anxiety levels in facing the competency test in Nurse Professional Students of Faletehan University in 2024. The method used is quantitative through a cross sectional design approach. The population of this study is 135 respondents with the number of samples determined by the Total Sampling Technique of 135 students. The results and analysis through the chi-square test obtained univariate results showed that (51.1%) respondents had high self-efficacy and (48.9%) had low self-efficacy. Meanwhile, students who are not anxious (51.9%) and students who are anxious (48.1%). The results of this bivariate analysis obtained a p-value of 0.032, at α=0.005 (p≤α) In conclusion, it can be concluded that there is a significant relationship. It is hoped that nursing students can further improve their self-efficacy so that they can be more confident when taking the exam.